2017
DOI: 10.15184/aqy.2016.266
|View full text |Cite
|
Sign up to set email alerts
|

The perfect storm: climate change and ancient Maya response in the Puuc Hills region of Yucatán

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…Altogether, these data indicate ceremonial activity spanning the entire indigenous occupation sequence suggesting native religious rituals performed here until the founding of Villa de Leyva. This water temple and alleged association with portrait statues [3] appears to be similar to a site documented by Silva [2,47] at the Salina de Mongua, a highland setting some 80 km to the east. Mountain stream channels (quebradas) empty into the Rio Leyva but must first pass through the Colonial heart of Villa de Leyva (Figure 2a).…”
Section: Terrace Platform and Stream Channelssupporting
confidence: 69%
See 2 more Smart Citations
“…Altogether, these data indicate ceremonial activity spanning the entire indigenous occupation sequence suggesting native religious rituals performed here until the founding of Villa de Leyva. This water temple and alleged association with portrait statues [3] appears to be similar to a site documented by Silva [2,47] at the Salina de Mongua, a highland setting some 80 km to the east. Mountain stream channels (quebradas) empty into the Rio Leyva but must first pass through the Colonial heart of Villa de Leyva (Figure 2a).…”
Section: Terrace Platform and Stream Channelssupporting
confidence: 69%
“…Recent climate change and human ecodynamic research in the Leiva Valley identified an engineered hydraulic landscape consisting of irrigation canals, check dams, drainage conduits, as well as potential raised-fields (artificially elevated planting surfaces) along river alluviums near the archaeological site of El Infiernito (Figure 1; see below) [2]. Prehispanic canals and raised-fields in the valley were reported to be still in use in the 16th century [3].…”
Section: A Hydraulic Landscape and Cosmologymentioning
confidence: 99%
See 1 more Smart Citation
“…These formations are primarily distributed according to climate (temperature and precipitation), soil type (e.g., volcanic, alluvial), and elevation (highlands and lowlands). Past [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and the transition between the two [21]. These changes in hydroclimate are reported to be primarily driven by the interactions of three climatic forces: (i) the position of the Inter Tropical Convergence Zone (ITCZ); (ii) the North Atlantic Oscillation; and (iii) the El Niño Southern Oscillation (ENSO) [22].…”
Section: Vegetationmentioning
confidence: 99%
“…), climate and drought (Smyth et al. ), and the struggles and strategies of enslaved colonial peoples (Hauser ).…”
Section: Addressing Current Issuesmentioning
confidence: 99%